Institutional development, financial deepening and economic growth: evidence from China - Iftekhar Hasan; Paul Wachtel; Mingming Zhou (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
There have been profound changes in both political and economic institutions in China over the last twenty years.Moreover, the pace of transition has led to variation across the country in the level of development.In this paper, we use panel data for the Chinese provinces to study the role of legal institutions, financial deepening and political pluralism on growth rates.The most important institutional developments for a transition economy are the emergence and legalization of the market economy, the establishment of secure property rights, the growth of a private sector, the development of financial sector institutions and markets, and the liberalization of political institutions.We develop measures of these phenomena, which are used as explanatory variables in regression models to explain provincial GDP growth rates.Our evidence suggests that the development of financial markets, legal environment, awareness of property rights and political pluralism are associated with stronger growth.
URN:NBN:fi:bof-201408072084
Keywords: O16; P14; P16; O53; 330